3D NUMERICAL HYDRODYNAMICAL SIMULATIONS OF A RADIATION-DRIVEN JET LAUNCH AND DISAPPEARING OVER LOW/HARD STATE - Nazarenko, V. V.; Nazarenko, S. V. (Одеські астрономічні публікації, 2016)
In the present research we have calculated 3D numerical hydrodynamical simulations of a radiation-driven jet launch and disappearing over low/hard state. The calculations show that the jet launch occurs at the beginning of the low/hard state over 10-30 minutes of the orbital time. The jet disappearing occurs over the short time scale (of the order of 10-30 minutes of the orbital time) at the end of the low/hard state. The calculations also show that the temperature near the accretor is increased in 100-200 times over low/hard state relatively high/soft. The mass accretion rate in the disc is anti-correlated with the temperature near the accretor in our calculations.